Cell wall contributes to the stability of plasma membrane nanodomain organization of Arabidopsis thaliana FLOTILLIN2 and HYPERSENSITIVE INDUCED REACTION1 proteins - Daněk, Michal; Angelini, Jindřiška; Malínská, Kateřina; Andrejch, Jan; Amlerová, Zuzana; Kocourková, Daniela; Brouzdová, Jitka; Valentová, Olga; Martinec, Jan; Petrášek, Jan (The Plant journal, 2020)
Current models of plasma membrane (PM) postulate its organization in various nano- and micro-domains with distinct protein and lipid composition. While metazoan PM nanodomains usually display high lateral mobility, the dynamics of plant nanodomains is often highly spatially restricted. Here we have focused on the determination of the PM distribution in nanodomains for Arabidopsis thaliana flotillin (AtFLOT) and hypersensitive induced reaction proteins (AtHIR), previously shown to be involved in response to extracellular stimuli. Using in vivo laser scanning and spinning disc confocal microscopy in Arabidopsis thaliana we present here their nanodomain localization in various epidermal cell types. Fluorescence recovery after photobleaching (FRAP) and kymographic analysis revealed that PM-associated AtFLOTs contain significantly higher immobile fraction than AtHIRs. In addition, much lower immobile fractions have been found in tonoplast pool of AtHIR3. Although members of both groups of proteins were spatially restricted in their PM distribution by corrals co-aligning with microtubules (MTs), pharmacological treatments showed no or very low role of actin and microtubular cytoskeleton for clustering of AtFLOT and AtHIR into nanodomains. Finally, pharmacological alteration of cell wall (CW) synthesis and structure resulted in changes in lateral mobility of AtFLOT2 and AtHIR1. Accordingly, partial enzymatic CW removal increased the overall dynamics as well as individual nanodomain mobility of these two proteins. Such structural links to CW could play an important role in their correct positioning during PM communication with extracellular environment.
Keywords: Cytoskeleton; lateral mobility; mikrotubuly; Arabidopsis Proteins; cytoskelet; tonoplast; membrane nanodomains; cell wall; membránové mikrodomény; membránové proteiny; proteiny huseníčku; plasma membrane; aktiny; Actins; buněčná stěna; Arabidopsis thaliana; hypersensitive induced reaction protein; Membrane Proteins; Microtubules; Arabidopsis; Membrane Microdomains; cytoskeleton; Microscopy, Confocal; konfokální mikroskopie; buněčná membrána; flotillin; Cell Wall; Cell Membrane